ADVANTAGES AND DISADVANTAGES OF ORGANIC AND TRADITIONAL POULTRY FARMING IN TERMS OF WELFARE - Кучерук, Марія (Modern engineering and innovative technologies, 2024)
The work examines the suffering of animals, their causes and the search for a solution to this issue. Excessive intensification of production in which it is not possible to care for animals as living beings,An alternative is the implementation of organic